Conservation education with religious values: A literature review - Maknun, Djohar; Muzzaki, Jajang Aisyul; Aripin, Ipin; Darmawan, Wawan (Universitas Wiralodra, 2024)
Environmental education and conservation education play crucial roles in cultivating an environmentally subject and conservation society. The purpose of this research was to describe the implementation of religiously charged conservation education and various learning methods that can be used in conservation education. This study focused on the implementation of religiously charged conservation education and exploring diverse learning methods applicable to conservation education. The literature study method is used to analyze various reference sources and synthesize them into an idea that is contextual to the relevant issue. The results of the literature review found that integrating religious value-charged conservation education can be one of the solutions to build awareness and concern for environmental sustainability. Religious values can be the individual spirit in instilling a positive attitude toward the environment so that it will build the spirit of religious conservationists. The planning of a conservation education program can generally be divided into three stages: the preparation, implementation, and evaluation stages of the program. For a Formal education setting, learning methods such as mini research, JAS, PjBL, and Field trips can be chosen as learning methods for conservation education effectively. In a non-formal education context, alternatives like extension, socialization, integration of local culture, and the like can be chosen as options for promoting conservation education.